FUNCTIONAL MYOCARDIAL CONDITION IN CHRONIC HEART FAILURE WITH CONCOMITANT OBESITY - V. Z. Netyazhenko; P. P. Bidzilya (Patologìâ)
Aims. To evaluate the functional myocardial condition in CHF of II functional class with abdominal obesity of different degree. Methods and results. 145 patients with CHF of II functional class, with normal weight, overweight and abdominal obesity I–III degrees were examined. Functional left ventricle myocardial condition in CHF depending on the degree of excess weight was studied. Overweight and abdominal obesity were diagnosed basing on the WHO criteria, the degree and abdominal (visceral) type of obesity were graded according to the common metric indices. Conclusion. The peculiarities of diastolic and systolic left ventricular function depending on the availability of overweight and obesity were revealed. Systolic dysfunction in CHF of II functional class is observed in a minority of patients, and the rate increases with the degree of overweight, and is maximal in a signifi cant obesity.